Tintinalli's emergency medicine a comprehensive study guide - Tintinalli, Judith E.; Stapczynski, J. Stephan; Ma, O. John; Cline, David, 1956-; Meckler, Garth D.; Yealy, Donald M. (McGraw-Hill Education, 2016)
The most widely used and highly regarded textbook and reference of emergency medicine. It is an important contemporary clinical emergency care resource for physicians, NPs, and PAs who practice emergency medicine and for emergency medicine and pediatric emergency medicine fellows.